MERUNDUK RAWAN (MERINTIS USAHA PENDUKUNG KELUARGA RAMAH PEREMPUAN) - Ramadhan, Gilang; Nurrohman, Bayu; Godjali, Moch. Rizky (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Sultan Ageng Tirtayasa, 2024)
Community Service held in Kadumerak Village aims to provide education and understanding to the community of Kadumerak Village, especially housewives, so that they can empower themselves more in order to increase household income. This community service is important because one of the problems that still plagues Pandeglang Regency is the high poverty rate, one of which is caused by the powerlessness of the community in encouraging themselves to try to increase income. This community service is one of the contributions made by Sultan Ageng Tirtayasa University in supporting community empowerment in order to improve the community's economy. The method in this community service is by implementing the stages of identifying problems in Kadumerak Village, then conducting field observations, and finally carrying out educational activities. The results of this program are that the community gets a good understanding of the use of technology and information to encourage the household businesses they run so that they can encourage an increase in community income gradually.